Extending mobile IP with adaptive individual paging a performance analysis. - Castelluccia, Claude
This paper proposes to extend Mobile IP with adaptive individual paging. Paging reduces the signaling cost of Mobile IP making it more adapted to wireless cellular IP networks. By reducing the number of location updates to be sent per mobile host, paging also minimizes power consumption of the mobile devices. In the proposed extension, each mobile host computes dynamically its optimal location area size according to its traffic and mobility parameters. The optimal size is the size that provides the best paging versus location update cost tradeoff and, as a result, minimizes the signaling load in the network. We compare, by simulation, the performance of the proposed scheme with that of Mobile IP [11], a paging scheme that uses fixed size location areas and Hierarchical Mobile IP [5]. We show that our extension provides a significant gain compared to Mobile IP and the fixed size paging scheme and performs as well and sometimes better than Hierarchical Mobile IP. We also show that the integration of adaptive individual paging within Hierarchical Mobile IP outperforms all schemes.